Resetting the epigenome: Methylation dynamics in cancer stem cells - Roy, Aiendrila; Padhi, Swati Shree; Khyriem, Ibakordor; Nikose, Saket; Sankar S. H, Harsha; Bharathavikru, Ruthrotha Selvi (Frontiers in Cell and Developmental Biology, 2022)
The molecular mechanisms that regulate stem cell pluripotency and differentiation has shown the crucial role that methylation plays in this process. DNA methylation has been shown to be important in the context of developmental pathways, and the role of histone methylation in establishment of the bivalent state of genes is equally important. Recent studies have shed light on the role of RNA methylation changes in stem cell biology. The dynamicity of these methylation changes not only regulates the effective maintenance of pluripotency or differentiation, but also provides an amenable platform for perturbation by cellular stress pathways that are inherent in immune responses such as inflammation or oncogenic programs involving cancer stem cells. We summarize the recent research on the role of methylation dynamics and how it is reset during differentiation and de-differentiation.